A Relevância do Conhecimento Histórico das Ginásticas na Formação e Atuação do Profissional de Educação Física - Figueiredo, Juliana Francica [UNESP]; Cynthia Franca Hunger, Dagmar Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2010)
The Gymnastics, in its extensive historical background, were part of the reasoning in the area now known as Physical Education. Deepening the knowledge from the historical Gymnastics during his education is extremely important for professional performance in Physical Education, as this knowledge can serve as a tool for the current configuration of the Gymnastics. Thus, this study presents a review of the literature that you want the frontline of the importance of historical knowledge Gymnastics during his education, is looking ahead to fetch reflect the current format of the same from an informed historically built as it is from the preservation of the knowledge that will be legitimized new avenues for the development of Gymnastics.

As Ginásticas, em sua extensa contextualização histórica, fizeram parte da fundamentação da área hoje conhecida como Educação Física. Aprofundar os conhecimentos históricos provenientes das Ginásticas durante a formação acadêmica é de suma importância para a atuação profissional em Educação Física, a medida que esses conhecimentos podem servir de ferramenta para a configuração atual das Ginásticas. Destarte, esse estudo apresenta uma revisão de literatura que pretende primar pela importância do conhecimento histórico das Ginásticas durante a formação acadêmica, perspectivando que se busque refletir o formato atual das mesmas a partir de um conhecimento historicamente construído, pois é a partir da preservação de referido conhecimento que serão legitimados novos caminhos ao desenvolvimento das Ginásticas.
The Relevance of Historical Knowledge of Gymnastics in the Formation and Operation of Physical Education Professional
Keywords: Gymnastics; History; Knowledge